Radiomodifying effect of the inozine complex with CO(II) in the irradiation C57BL/6 line mice - Veyalkina, Nataliya N.; Kadukova, Alena M.; Tsukanova, Alena V.; Shafarost, Kristina N.; Fabusheva, Kseniya M.; Abdullayev, Asim S.; Shamilov, Elshan N. (Journal of the Belarusian State University. Ecology, 2020)
The study of new radioprotective compounds modifying the damaging effects of ionizing radiation is important issue of radiobiology.The aim of this research was to study of the anti-radiation properties of inosine and inosinate cobalt (II) after acute single exposure γ-radiation.The experiment was performed in C57Bl/6 mice of both sexes. To assess the radioprotective effect of the test compound the animals were irradiated to different dosages 5Gy, 6Gy, 7Gy, 8Gy, the observation was carried out for 30 days. To assess the effect of the test compound on the level of micronuclei in polychromatophilic erythrocytes of the bone marrow and the level of cell death of peripheral blood lymphocytes, the animals were irradiated of dose 1.5 Gy, the animals were euthanized 48 h post irradiation. Solutions of inosine and Co(II)inosinate were administered intraperitoneally at a dose of 45 mg/kg 15 minutes after irradiation. The Co(II)inosinate, was provided by the Institute of Radiation Problems of the National Academy of Sciences of Azerbaijan. There was an increase in the survival of animals which were injected the solution of inosine and Co(II)inosinate when compared to the radiation group alone. No significant effect was found on the restoration of thecellular composition of peripheral blood leukocytes in animals one month after irradiation at dose of 5 Gy. The decrease in the number of cells with micronuclei and a reduced number of lymphocytes at the stage of early and late apoptosis was observed in groups of animals which were injected the solution of inosine and Co(II) inosinate.
Keywords: Inosine; Co(II) inosinate; radiomodification; γ-radiation; C57Bl/6 mice